An Analysis of Swear Words Used by the Teenagers in Singaraja - ., Intania Harismayanti; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin; ., Dewa Putu Ramendra, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
This study aimed at analyzing swear words used by the teenagers in Singaraja. To accomplish this goal, this study used a descriptive qualitative research, which was conducted by observing, audio recording, and interviewing the subjects. The subjects of this study were 10 teenagers originally from Singaraja. The results of the study showed that swear words used by the teenagers in Singaraja have their forms, references, and functions. There were three forms of swear words: (1) in the form of words, which also are subdivided into two: monomorphemic (pirate ‘ancestors’, pletan ‘male genital’, teli ‘female genital’, etc.) and polymorphemic (matan ‘eyes’, polone ‘brain’, bangkaan ‘dead body’, etc.), (2) in the form of phrases (ndas teli ‘female genital’, lengeh buah ‘so crazy’, ngamah gen ‘always eat’, etc), and (3) in the form of clauses (lengeh ti cai ‘you are so crazy’, gebuh bungut nanine ‘you are a liar’, liak cai ‘you are the devil’,etc.). The references of the swear words were related to: (1) religion, (2) body function, (3) excrement, (4) animals, (5) activity, (6) personal background, (7) mental illness, (8) devils, (9) kinship. The functions of those swear words were: (1) to draw attention, (2) to provide catharsis, (3) to provoke, (4) to create interpersonal identity, (5) integrative, (6) aggressive, (7) regressive, and (8) emphasis. keyword : forms, functions, references, swear words